Regional variation in the prevalence of undernutrition and its correlates among under 5 year children in Western India - Meshram, Indrapal I; K., Mallikharjuna Rao; K., Sreeramakrishna; R., Harikumar; K., Venkaiah; A., Laxmaiah (Indian Journal of Community Health, 2019)
Background: undernutrition is an important public health problems in India with more than 40% children under 5 years are undernourished. Objectives: To assess prevalence of undernutrition, regional variation and its correlates among under 5 year children. Materials & Methods: A community-based, cross-sectional study was carried out in all the districts of Gujarat covering all regions, using systematic sampling to assess nutritional status of under 5 year children. Nutritional assessment was done using WHO child growth standard. Results: The overall prevalence of underweight, stunting and wasting was 44%, 42% and 20% respectively. The prevalence of undernutrition was significantly (p<0.01) higher in central region (52.4%, 49.1% & 24.2% respectively) as compared to Saurashtra & Kachchh region (31.1%, 34.9%, 12.3% respectively). Minimum dietary diversity was more in Sourashtra region (87%) and low in North region (78%). The odds of undernutrition was significantly higher among children belonging to Scheduled tribe communities (OR: 1.62, 1.46 & 1.61 respectively), children of illiterate mothers (OR: 1.23, 1.24 & 1.18 respectively), among children belonging to lower socio-economic groups (OR: 1.39, 1.23 & 1.18 respectively) and with history of morbidity and hygienic practices of mother. The odds of underweight and stunting was 1.3 times higher among children from households not having sanitary latrine and separate kitchen. Conclusions: The prevalence of undernutrition was high in central as compared to Saurashtra & Kachchh region and is associated with community, household income, sanitary latrine and literacy status of mother. Therefore, multi-component health and nutrition intervention along with improving household income, sanitation and hygiene may help in prevention and control of undernutrition.